A study on open air defecation practices among the population above 6 years in rural field practice area of Santhiram Medical College, Nandyal, Kurnool dist, Andhra Pradesh - M., Venkateswarlu (International Journal Of Community Medicine And Public Health, 2019)
Background: Open air defecation can be defined as the excretion of human excreta in open places such as park, roadside, vegetable patch, agricultural fields and railway track other than toilets. Open air defecation may leads to various health problems such as soil pollution, water pollution, contamination of foods and propagation of flies. Nearly 74% of India’s population live in rural areas and the majority of them “go to the fields” for defecation and thereby pollute the environment with human excreta. The aims and objectives of the study were to find the association between defecation practices and socio-demographic variables; to assess the prevalence of hook-worm infestation and anemia among them. Methods: A cross sectional study was conducted. Sample size was 550 and simple random sampling. Chi-square test was applied. Results: The prevalence of open air defecation was 441 (80.2%). 270 (61.2%), 171 (38.8%) were males and females; 23.3% were habit of hand washing with soap after toilet. 87 (19.7%), 63 (14.3%), 43 (9.7%) were found to be having hook worm, round worm, and pin worm infestation in the stool examination. 32 (35.5%), 21 (23.3%), 37 (41.1%) were having severe anemia, moderate anemia, and mild anemia. Conclusions: 335 (60.9%), 106 (19.3%) people were going for open air defecation and inspite of having toilet at home. 226 (51.2%) belong to lower socio economic class. The association between socio demographic profile and open air defecation was significant (χ2=0.02, p<0.05).